2009
DOI: 10.1007/s00247-009-1198-5
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary stalk duplication with intrasellar dermoid and herniation of the third ventricle

Abstract: An 11-year-old boy with short stature (height 111 cm) had a weight of 19 kg and a bone age of 5 years. There were low levels of all the anterior pituitary hormones, but no evidence of central diabetes insipidus. Coronal MR images ( Fig. 1) showed duplication of the pituitary infundibulum (arrowheads) and hypothalamus (arrows). A well-defined T1-hyperintense lesion consistent with a dermoid (star) was seen within the sella between the duplicated stalks. Sagittal images (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…Both ROBO1 deletion and thyroid transcription factor-1 gene deletion has been associated with pituitary stalk duplication; however, no other common ground could be sought amongst the described cases in the literature. Only herniation of the third ventricle was something described in two of the reported cases, 6,7 which can explained embryologically as the infundibular process descends from the floor of the third ventricle. Interestingly, none of the patients with DPS had non-vascular craniocervical abnormalities.…”
Section: Discussionmentioning
confidence: 95%
“…Both ROBO1 deletion and thyroid transcription factor-1 gene deletion has been associated with pituitary stalk duplication; however, no other common ground could be sought amongst the described cases in the literature. Only herniation of the third ventricle was something described in two of the reported cases, 6,7 which can explained embryologically as the infundibular process descends from the floor of the third ventricle. Interestingly, none of the patients with DPS had non-vascular craniocervical abnormalities.…”
Section: Discussionmentioning
confidence: 95%
“…Both cases were associated with other findings, including nasopharyngeal teratoma and macroadenoma. Other case reports of pituitary stalk duplication were associated with other abnormalities, including intrasellar dermoid cyst [ 12 ] and duplication of the hypothalamus [ 13 ], among others. Our patient had pituitary stalk duplication, with third ventricle sagging and PES.…”
Section: Discussionmentioning
confidence: 99%
“…Herniation of the third ventricle compresses the pituitary gland and fills the sella turcica with CSF fluid which leads to pituitary hypoplasia. Other case reports of pituitary stalk duplication were also associated with third ventricle herniation, but empty sella turcica was not found on imaging [ 12 , 13 ]. In these two case reports, symptoms were reported early in childhood.…”
Section: Discussionmentioning
confidence: 99%
“…We identified a total of 48 additional cases in 39 papers from 1931 to 2013 (Feller, ; Brodsky, ; Clausnitzer, ; Morton, ; Rintala and Ranta, ; Bale and Reye, ; Hori, ; Wittkampf and van Limbourgh, ; Trotman and McNamara, ; Kollias et al, ; Shah et al, ; Hamon‐Kérautret, ; Lu et al, ; Vandenhaute et al, ; Uchino et al, ; Shroff et al, ; Spencer, ; Haghighi et al, ; Mutlu et al,2004; Goldstein and Drugan, ; Huisman et al, ; Slavotinek et al, ; Noguchi et al, ; Stewart et al, ; Jank et al, ; Bhattacharya et al, ; Madhusudhan and Kandpal, ; Joethy et al, ; Calda et al, ; Chariker et al, ; Kumar et al, ; Bonet et al, ; Manjila et al, ; Prakash et al, ; Rabelink et al, ; Ginat et al, ; Maeda et al, ; Shen et al, ; Tsai et al, ). All cases were sporadic.…”
Section: Reviewmentioning
confidence: 99%
“…Diagnosis was made prenatally due to an abnormal ultrasound scan in 4 instances, neonatally for overt craniofacial malformations in 34 cases, and later in postnatal life in 6 cases. The latter group comprises a 9‐month‐old girl ascertained for upper airway obstruction (Bhattacharya et al, ), a 9‐year‐old girl with supernumerary permanent maxillary incisors (Trotman and McNamara, ), a 11‐year‐old boy for growth retardation due to hypopituitarism (Madhusudhan and Kandpal, ), a 16‐year‐old young woman for delayed sexual development (Kollias et al, ), a 38‐year‐old woman for galactorrhea and hyperprolactinemia (Rabelink et al, ), and a 40‐year‐old woman in whom the teratoma was serendipitously identified during investigations for breast cancer (Ginat et al, ). Standard karyotyping was performed in five cases with normal results (Hori, ; Slavotinek et al, ; Manjila et al, ; Maeda et al, ).…”
Section: Reviewmentioning
confidence: 99%